1976
DOI: 10.1073/pnas.73.6.1999
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of calcium binding in cerebral tissue to weak environmental electric fields oscillating at low frequency.

Abstract: Weak sinusoidal electric fields modify the calcium efflux from freshly isolated chick and cat cerebral tissues bathed in Ringer's solution, at 360. Following incubation (30 min) with radioactive calcium (45Ca2+), each sample, immersed in fresh solution, was exposed for 20 min to fields at 1, 6, 16, 32, or We have previously described a sharply increased efflux of calcium from isolated chick brain tissues exposed to modulated radio frequency fields (16). These studies showed that the response depended on a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 386 publications
(154 citation statements)
references
References 30 publications
6
143
1
Order By: Relevance
“…If in some kind of cells there is an upper limit for this value of membrane potential change, then the channel would be gated whenever the force exerted on its sensors is within this 'window'". Five of these studies show effects on [Ca2+] i fluxes (24)(25)(26)(27)(28), consistent with possible roles of VGCCs. These studies provide strong evidence that these window effects occur at levels where there is either no measured change in temperature or extremely low heating.…”
Section: Three Other Types Of Observations That Contradict the Assumpmentioning
confidence: 74%
See 1 more Smart Citation
“…If in some kind of cells there is an upper limit for this value of membrane potential change, then the channel would be gated whenever the force exerted on its sensors is within this 'window'". Five of these studies show effects on [Ca2+] i fluxes (24)(25)(26)(27)(28), consistent with possible roles of VGCCs. These studies provide strong evidence that these window effects occur at levels where there is either no measured change in temperature or extremely low heating.…”
Section: Three Other Types Of Observations That Contradict the Assumpmentioning
confidence: 74%
“…It has been shown that there can be intensity "windows" where biological activity is greater than at intensities both higher and lower than the window intensity (24)(25)(26)(27)(28)(29)(30)(31)(32). This again argues against a heating mechanism as there are no known thermal dose-response curves with similar windows.…”
Section: Three Other Types Of Observations That Contradict the Assumpmentioning
confidence: 89%
“…Nonionizing radiation has been shown to cause endocrine (12), neurologic (13), and immunologic (14) changes in animals. Weak oscillating electric fields have been shown to affect calcium binding to cerebral tissue (15), and weak pulsedmagnetic fields have been shown to be teratogenic for the developing chicken (16). In most cases, these effects do not show the usual dose-response relationships.…”
Section: Methodsmentioning
confidence: 96%
“…For an implanted insulated wire, with conductor radius a, insulation radius b, insulation dielectric constant Cd , and the end of the conductor in direct contact with the tissue, the anhancement factor may be expressed as C IfeC (k (17) For a frequency of 450 MHz withEA -2.25 and'b/-a -2, the enhancement factor given above may be expressed in terms of the ratio of wire length of radius:…”
Section: Guy Et Almentioning
confidence: 99%